The Mediating Role of Difficulty in Emotion Regulation in the Relationship Between Traumatic Life Events and Character With Negative Symptoms of Schizophrenia - Razmyar, Hadi; Mansouri, Ahmad; Ahi, Qasem; Bahreinian, Seyed Abdolmajid; Saied, Fahime (Iranian Journal of Neurodevelopmental Disorders, 2024)
This study aimed to investigate the mediating role of difficulty in emotion regulation in the relationship between traumatic life events and character with negative symptoms of schizophrenia. The research method was quantitative, fundamental, cross-sectional, descriptive, and correlational. The statistical population included all people with schizophrenia hospitalized in Razi Psychiatric Hospital in 2023-2024, of which 200 people were selected by convenience sampling. The data collection tools included the Positive and Negative Symptom Scale, the Temperament and Character Inventory, the Trauma History Questionnaire, and the Short Form of Difficulty in Emotion Regulation. SPSS and AMOS software were used to analyze the data, as well as Pearson correlation and structural equation modeling. The direct coefficient analysis showed that the relationship between traumatic life events and difficulty in emotion regulation with negative symptoms of schizophrenia was significant. Another finding of the study showed that the direct effect of traumatic life events and character on difficulty in emotion regulation was significant. Indirect coefficients indicated that the indirect effect of traumatic life events and character on negative symptoms of schizophrenia was significant with the mediating role of difficulty in emotion regulation. Finally, the present study’s model had a favorable fit (CFI=0.97, NFI=0.95, IFI=0.97, GFI=0.97, RMSEA=0.071). Therefore, emotion regulation training can be considered an important approach to treating the challenging task of schizophrenia’s negative symptoms.